To repair, reconstruct, replace & reduce: upper limb injuries amongst other orthopaedic problems - Arumugam, Manohar (Universiti Putra Malaysia Press, 2018)
Injuries of the limbs are very common from many different causes, and can be devastating to the patient as it may lead to a range of functional deficits which unless managed properly, can result in death or loss of the limb. Injuries to the limb can be treated by skilful neglect or by performing various surgical procedures, ranging from simple debridement to complex reconstructive procedures or replacement of the defective part. Challenges in treating limb injuries include limited availability of operating theatre time for general anaesthesia, but for hand injuries this can sometimes be overcome by using local anaesthesia. Although there are problems with the use of local anaesthesia, there are ways to resolve these problems. The injured limb is often swollen, obscuring landmarks which locate the site of surgical incision. Sometimes direct repair of the injured part may not be possible, and the use of parts harvested from the patient may be required. It is important to know if the length of the harvested parts is adequate, and this can be estimated using a mathematical formula. The outcome of the treatment also has to be assessed to determine if the patient has improved following treatment. While injury can be caused by accidents, it can also be the result of improper use of a daily object, improper posture, and repetitive use of office equipment. Although rare, injuries can also be inflicted by the patient for various reasons. These self-inflicted injuries can mimic other pathological conditions, and could lead to a wrong diagnosis if not recognized. Injuries can also result in ganglion cyst, a benign condition which can occur in rare locations such as the proximal interphalangeal joint. Besides that, injuries from plant thorns and cat bites can result in fungal infections whereas squamous cell carcinoma of the nailbed is believed to be related to preceding trauma. Injuries that occur at the office are usually musculoskeletal disorders and can be prevented by proper measures. Exercises can help prevent and treat musculoskeletal disorders. Joints that cannot be repaired need to be replaced using joint prosthesis and the commonly used joint prosthesis are for the knee and hip. The use of different materials and configurations can affect the rate of wear and tear as well as loosening of the prosthesis. Meanwhile, understanding of the forces acting on the femoral femur bone is essential in developing a good prosthesis for the hip, whereas finite element analysis is used to study the stress acting on the bone. While the treatment of injuries is important, the prevention of injuries should be given just as much attention and importance. Injuries caused by motor vehicle accidents can be prevented by understanding the injury mechanism and by developing preventive strategies. This may be aided by the use of computer simulation using finite element models and crash test dummies which can help in understanding the mechanism of injury and designing better safety devices. Hence the study of limb injuries and musculoskeletal disorders is diverse in its requirements for solutions that range from treatment as well as prevention.